Inflation, output, and welfare in the laboratory - Janet Hua Jiang; Daniela Puzzello; Cathy Zhang (Bank of Canada, 2023)
We develop an experimental framework to investigate the quantity theory of money and the real effects of inflation in an economy where money serves as a medium of exchange. We test the classical view that inflation reduces output and welfare by taxing monetary exchange. Inflation is engineered by constant money growth. We conduct three treatments, where the newly issued money is used to finance government spending, lump-sum transfers, and proportional transfers, respectively. Experimental results largely support theoretical predictions. Higher money growth leads to higher inflation. Output and welfare are significantly lower with government spending, and output is significantly lower with lump-sum transfers, while there are no significant real effects with proportional transfers. A deviation from theory is that the detrimental effect of money growth in our framework depends on the implementation scheme and is stronger with government spending than with lump-sum transfers.
Keywords: C92; D83; E40; 330; inflation and prices; inflation: costs and benefits; monetary policy